If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -29 = 8(3 + -1x) + -283 Reorder the terms: -29 + 12x = 8(3 + -1x) + -283 -29 + 12x = (3 * 8 + -1x * 8) + -283 -29 + 12x = (24 + -8x) + -283 Reorder the terms: -29 + 12x = 24 + -283 + -8x Combine like terms: 24 + -283 = -259 -29 + 12x = -259 + -8x Solving -29 + 12x = -259 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -29 + 12x + 8x = -259 + -8x + 8x Combine like terms: 12x + 8x = 20x -29 + 20x = -259 + -8x + 8x Combine like terms: -8x + 8x = 0 -29 + 20x = -259 + 0 -29 + 20x = -259 Add '29' to each side of the equation. -29 + 29 + 20x = -259 + 29 Combine like terms: -29 + 29 = 0 0 + 20x = -259 + 29 20x = -259 + 29 Combine like terms: -259 + 29 = -230 20x = -230 Divide each side by '20'. x = -11.5 Simplifying x = -11.5
| 3+2.7x=9.5+3.2x | | ln(5x(x+3))=4 | | 11x+5=9+21 | | -5x-3=-27 | | 6z+3=17-z | | o(n)=2(5)-1 | | -13+x=32 | | 4y+9y+8y+5= | | 17y-13+6y^2-14y+5= | | 5(x^2)+15x=e^4 | | C=30+0.7Y | | 28(2x-1)=7(x+3)2x | | 2+4(x-1)=5-8(x-7) | | 28(2x-1)=7(x+3)22x | | -2x+63=-49+6x | | 76=15.7xh^2 | | 10-x=65 | | 2x+27=2x-11 | | 4b+-8=2b+6-4b+13 | | 0=-16t^2+0t+64 | | n+0.6+n=n+0.1+2n | | 7.5+1x=2.5x | | Y/12=17/13 | | 12x+(30-2x)+12x=144 | | 7x+5x-6=2x+6 | | 62735/628358=x | | 15=5(n-8) | | log(7)(6x-5)=2 | | 4x-21=x+21 | | 17+x=-8 | | 72+19362/56=x | | 9/10 |